A new species of Coronatella Dybowski & Grochowski, 1984 (Cladocera: Chydoridae) endemic to Jeju Island (Republic of Korea) - Sinev, Artem Y.; Lee, Wonchoel; Kotov, Alexey A. (Zootaxa, 2022)
Recently particular attention of cladocerologists has focussed on a subtropical-southern temperate zone of the Far East of Eurasia comprising a center of water flea (Crustacea: Cladocera) endemism. Two endemic taxa were described previously from Jeju Island (Republic of Korea), but still the cladocerans of this island are poorly known. The aim of this communication is to describe a new species of Coronatella (Coronatella) Dybowski & Grochowski, 1894 (Anomopoda: Chydoridae) and discuss diagnostic characters of this taxon with reference to their diagnostic value in other cladoceran groups. Surprisingly, all characters discriminating C. (C.) jejuana sp. nov. from closest C. (C.) rectangula (Sars, 1862) are from the set suggested for chydorid species delimitation by Nikolai Smirnov more than 50 years ago. Therefore, a search for diagnostic characters of a potentially new taxon could concentrate on just some potentially important structures. However, a program of detailed redescriptions of previously established taxa is necessary for an adequate description of new taxa which are congeners of the former, and such comprehensive work is still in its infancy.